The Significance of “Smart Specialisation” for the Regional Innovativeness Growth - Magdalena KOGUT-JAWORSKA; Elżbieta OCIEPA-KICIŃSKA (Communications of International Proceedings, 2020)
This article analyses the significance of smart specialisations in enhancing the innovative policy paradigm in the regions. Smart specialisations by definition should play a major role in stimulating innovativeness at the regional level, in particular with regard to enhancing the region’s potential, its resources, key competences and competitive advantages while identifying the priority criteria. Thus, the concept should ensure a bigger growth of the regions attractiveness and their faster development. Smart specialisation is an approach implemented under the EU’s Cohesion Policy, also in Poland. Smart specialisation in Polish regions is also known as an approach that combines the industrial, educational and innovative policies in order to identify and concentrate a limited number of priority areas for the economy. It is assumed that clearly identified smart specialisations in combination with appropriate management of public financial resources contribute to economic growth and improvement of the economic situation in Polish regions. The aim of this article is to present and characterise the assumptions for smart specialisations, and also to explore the process of intelligent specialisation and its role in the growth of innovativeness in Polish regions. First, the article presents the assumptions for introducing smart specialisation and characterises the smart specialisations identified by the individual regions in Poland. Next, the research assumptions are presented along with the results of the regional benchmarking based on the synthetic measure of development and on the analysis based on indicators for strategic horizontal objectives, describing the level of innovativeness and R&D advancement.
Keywords: Smart Specialisation; Regional Policy; EU Financial Policy; Innovation; Economic Development